2015
DOI: 10.1007/s13524-015-0450-x
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic-White Differences in Lifespan Variability in the United States

Abstract: This study is the first to investigate whether and, if so, why Hispanics and non-Hispanic whites in the United States differ in the variability of their lifespans. Although Hispanics enjoy higher life expectancy than whites, very little is known about how lifespan variability—and thus uncertainty about length of life—differs by race/ethnicity. We use 2010 U.S. National Vital Statistics System data to calculate lifespan variance at ages 10 and older for Hispanics and whites, and then decompose the Hispanic-whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 49 publications
5
26
0
Order By: Relevance
“…Previous research on lifespan variability has shown similar patterns at the subnational level. Lariscy et al (2016) also found that most of the difference in lifespan variance between Hispanics and Whites in the US is due to the large age dispersion (spread effects) of diseases. Despite the generalized mortality disadvantage of LAC, some countries, such as Argentina, Chile, Costa Rica, Cuba, and Uruguay, have experienced rapid progress over recent decades, which has led them to achieve similar life expectancies and lifespan variability to those seen in the developed world.…”
Section: Discussionmentioning
confidence: 95%
“…Previous research on lifespan variability has shown similar patterns at the subnational level. Lariscy et al (2016) also found that most of the difference in lifespan variance between Hispanics and Whites in the US is due to the large age dispersion (spread effects) of diseases. Despite the generalized mortality disadvantage of LAC, some countries, such as Argentina, Chile, Costa Rica, Cuba, and Uruguay, have experienced rapid progress over recent decades, which has led them to achieve similar life expectancies and lifespan variability to those seen in the developed world.…”
Section: Discussionmentioning
confidence: 95%
“…While in Central and Eastern European countries, changes in alcohol consumption were directly linked to fluctuating lifespan variation (Aburto and van Raalte, 2017). The role external causes of death play in determining lifespan variation levels extents to studies of population subgroups (Lariscy et al, 2016; Nau and Firebaugh, 2012; van Raalte et al, 2018). The value of lifespan variation is that it is sensitive to these mortality premature mortality crises.…”
Section: Discussionmentioning
confidence: 99%
“…The median age of the US Hispanic population is 27 years, as compared to the US population (37 years) and NHWs (42 years) [ 29 , 30 ]. Life expectancy at birth is longer for Hispanics (79.1 years for males, 83.8 for females) than for NHWs (76.5 years for males, 81.2 for females) (23), and Hispanics have a lower lifespan variability than do NHWs [ 31 ]. The growth of the US Hispanic population has created a significant racial/ethnic generational gap in the USA; in 2010, 34.9% of Hispanics were under the age of 18 compared to 20.9% of NHWs [ 32 ].…”
Section: Methodsmentioning
confidence: 99%